2020
DOI: 10.1002/fsn3.2089
|View full text |Cite
|
Sign up to set email alerts
|

Alternative antibiotic feed additives alleviate pneumonia with inhibiting ACE‐2 expression in the respiratory system of piglets

Abstract: Weaning piglets often suffer from pneumonia during growth, so in general, antibiotics are used by owners to make piglets grow smoothly. However, antibiotics may be accompanied by many side effects such as gastrointestinal discomfort and allergies. The aim of this study was to develop an alternative antibiotic herbal veterinary medicine for alleviating pneumonia in weanling piglets. As observed in the pig ranches, many weanling piglets suffer from the pneumonia and also show high expression of angiotensin‐conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…In fact, following the ban on the use of antibiotics as growth promoters, therapeutic antibiotics and zinc oxide have become more widely used [7][8][9] to prevent porcine colibacillosis, improve suboptimal weight gain, and feed efficiency. Alternatives to antibiotics and zinc oxide are also urgently needed to guarantee the profitability of swine farming, particularly during weaning, which involves the largest use of antimicrobials due to the high incidence of gastroenteric disorders and multifactorial post-weaning diarrhoea (PWD) [10,11]. The gastrointestinal tract (GIT) is a highly specialised organ where the dynamic interaction between host cells and the complex environment (mucosal chemical barrier, immune system, and epithelium) impacts on gut health [12].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, following the ban on the use of antibiotics as growth promoters, therapeutic antibiotics and zinc oxide have become more widely used [7][8][9] to prevent porcine colibacillosis, improve suboptimal weight gain, and feed efficiency. Alternatives to antibiotics and zinc oxide are also urgently needed to guarantee the profitability of swine farming, particularly during weaning, which involves the largest use of antimicrobials due to the high incidence of gastroenteric disorders and multifactorial post-weaning diarrhoea (PWD) [10,11]. The gastrointestinal tract (GIT) is a highly specialised organ where the dynamic interaction between host cells and the complex environment (mucosal chemical barrier, immune system, and epithelium) impacts on gut health [12].…”
Section: Introductionmentioning
confidence: 99%
“…The herbal formula GLZ was investigated as an alternative medicine for weanling piglets. The formula can alleviate respiratory allergies and prevent pneumonia in weanling piglets by inhibiting ACE-2 expression in the respiratory system [ 20 ]. However, little is known regarding the underlying pharmacological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…A component of GLZ, Guizhi, is a traditional herbal preparation that has been used to treat head-related illnesses such as fever, headache, sweating, and wind-induced headaches [ 22 ]. Chromatographic investigation of Guizhi in our previous research [ 20 ] revealed that its bioactive substances are coumarin, cinnamic acid, cinnamaldehyde, and 2-methoxycinnamaldehyde. Coumarin has been used in various products and candidate drugs because coumarin compounds have high bioavailability and both antioxidant and anti-inflammatory properties [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations